Laparoscopic distal gastrectomy demonstrates acceptable outcomes regarding complications compared to open surgery for gastric cancer patients with pylorus outlet obstruction - Wang, Sen; Zhang, Yigang; Chen, Zetian; Li, Qingya; Li, Fengyuan; Li, Zheng; Liu, Hongda; Xuan, Zhe; Xia, Yiwen; Xu, Penghui; Fang, Lang; Wang, Linjun; et al. (Frontiers in Oncology, 2023)
Background: For gastric cancer (GC) patients with pylorus outlet obstruction (POO), whether laparoscopic surgery has advantages over open surgery remains unclear. This study aims to investigate the differences between patients with and without POO in open and laparoscopic groups and to determine the differences between laparoscopic distal gastrectomy (LDG) and open distal gastrectomy(ODG) in GC patients with POO. Methods: A total of 241 GC patients with POO who underwent distal gastrectomy at the Department of Gastric Surgery of the First Affiliated Hospital of Nanjing Medical University between 2016 and 2021 were included in this study. A total of 1121 non-POO patients who underwent laparoscopic surgery and 948 non-POO patients who underwent open surgery from 2016 to 2021 were also enrolled in the study. We compared complication rates and hospital stays between open and laparoscopic groups. Results: There was no significant difference for LDG between GC patients with and without POO regarding the overall complication rates (P=0.063), Grade III-V complication rate (P=0.673) and anastomotic complication rate (P=0.497) from 2016-2021. The patients with POO had longer preoperative hospital stay (P=0.001) and post-operative hospital stay (P=0.007) compared to patients without POO. No significant difference was observed for open patients between POO and non-POO patients regarding overall complication rate (P=0.357), grade III-V complication rate (P=1.000) and anastomosis-related complication rate(P=0.766). Compared with open surgery in GC patients with POO (n=111), the total complication rate of LDG group was 16.2%, which was significantly lower than that of open group (26.1%, P=0.041). No significant differences in Grade III-V complication rate (P=0.574) and anastomotic complication rate (P=0.587) were observed between laparoscopic and open groups. Patients receiving laparoscopic surgery had shorter post-operative hospital stay than open surgery (P=0.001). More resected lymph nodes (LN) were also observed in laparoscopic group (P=0.0145). Conclusion: The comorbidity of GC with POO does not increase the complication rate after laparoscopic or open distal gastrectomy. In GC patients with POO, laparoscopic surgery shows advantages over open surgery with lower overall complication rate, shorter post-operative hospital stay and more harvested lymph nodes. Laparoscopic surgery is a safe, feasible and effective treatment for GC with POO.